Reação de genótipos de cafeeiro à Hemileia vastatrix e à Cercospora coffeicola - Madeira, José Augusto Pereira (2016)
Coffee plants were introduced in Brazil in the Northern State of Para around 1727. Two major diseases have affected coffee trees in the country. One is rust, caused by fungus Hemileia vastatrix and accountable for production losses up to 50%. The other one is Cercospora leaf spot, caused by fungus Cercospora coffeicola endemic to all Brazilian coffee farms and, therefore, economically critical due to production losses both in the plant nursery and in the field. Availability of resistant varieties has been a constant challenge for breeders. Research programs play an important role in the search for new resistant and/or tolerant genotypes, since over time plants can become susceptible to new, genetically variable races of pathogens. This study aimed to evaluate the incidence and severity of such diseases, the resistance of different coffee genotypes to H. vastatrix and C. coffeicola pathogens, as well as the productivity of said genotypes in dense planting system. The experimental design consisted of randomized blocks, with twelve genotypes (treatments) and two replications (blocks). SISVAR® program was used to analyze data and compare them building on Scott-Knott test and Tukey’s test with a probability of 5%. Disease incidence and severity percentage were assessed for both Cercospora leaf spot and rust. Means were used to calculate the area under the disease progress curve (AUDPC) of both diseases. As to rust, the most resistant genotypes were H586-6, IBC 12, and H556-7 H567-6. As to Cercospora leaf spot and productivity, no statistical differences were found across genotypes. The dense planting system did not impair plant development, but favored disease evolution given the microclimate it produces.